Cricopharyngeal Achalasia Presenting as Acute Dysphagia in a Pediatric Patient. (September 2022) - O'Neill, Laura Beth; Magyar, Matthew; Reilly, Brian; Gayle, Tamara
Objective: To describe a case of idiopathic cricopharyngeal achalasia (CPA) in a pediatric patient with acute onset of dysphagia managed conservatively with supportive care. Methods: Sixteen-month-old boy presented with acute onset of gagging and coughing with feeding. His exam was notable for a well-appearing child with pooling of oral secretions and coarse breath sounds. Plain film series did not show radio-opaque foreign body (FB) and an esophagram demonstrated an endoluminal filling defect of the cervical esophagus and aspiration of contrast. He was taken to the operating room for urgent endoscopy but no FB or food impaction was observed. He had persistent symptoms that required further evaluation and a multidisciplinary team approach. Bedside laryngoscopy did not reveal any abnormalities. Modified barium swallow (MBS) study revealed upper esophageal sphincter (UES) dysfunction, consistent with cricopharyngeal achalasia. Repeat upper endoscopy with biopsies demonstrated mucosal irritation overlying the UES but histologic studies were negative for infectious causes. Results: He was treated with supportive care, including nasogastric feedings for nutrition supplementation as he was unable to tolerate oral feedings without aspiration. Over the course of 3 months after discharge, his symptoms resolved and repeat MBS was normal. Conclusion: CPA is a rare cause of dysphagia in the pediatric population. Conservative management with supportive care is a reasonable approach in cases with acute onset in otherwise healthy children without underlying medical problems.